Formação de magistrados : as competências requisitadas do juiz como referências para as ações de seleção e formação da magistratura nacional - Selau, Isabel Cristina Lima (2019)
This dissertation was developed in the Postgraduate Program in Education (PPGEDU) of the Pontifical Catholic University of Rio Grande do Sul (PUCRS), with the orientation of the line of research Training, Policies and Practices in Education. The research sought to investigate the competences (knowledge, skills and attitudes) to be required of the magistrate, in his work practice, for an efficient, expeditious and effective judicial service that meets the demands of an increasingly complex and demanding society. The purpose of this work is to study the models of judicial education in international justice systems and especially the educational project proposed by the National School for the Training and Improvement of Magistrates, aiming at the initial and continuous training of Brazilian judges. This new model is centered on a pedagogical project that seeks to overcome the traditional processes of legal formation, presenting a teaching-learning proposal centered on the development of competencies to be required of the judge for a judicious performance of quality, having as presuppositions: ethics and humanism as principles of all formative action; interdisciplinarity in the treatment of content; articulation between theory and practice; and jurisdictional practice as a starting point for the selection and organization of contents. The autonomy and protagonism of the judge-student and his previous experiences are valued. The theoretical basis used is based on authors such as Perrenoud, Le Boterf, Zabala, Morin, Pérez Gómez, in the area of education; and Nalini, Dallari, Cappelletti, Wernneck, in the area of Law; among others. The research had an exploratory and quantitative qualitative approach, based on the teachings of Malhotra (2005), through a case study (YIN, 2010). The target audience consisted of federal and state magistrates from some of the country’s courts, with the following instruments: semi-structured interviews (qualitative part) and structured questionnaire (quantitative part). The data were analyzed, in their qualitative contribution, through the Discursive Textual Analysis technique (MORAES; GALIAZZI, 2011); and, in the quantitative part, through descriptive and multivariate statistics (MALHOTRA, 2005). The results of the study identified four groups of competencies that magistrates will be required to perform in their work practice: socio-communicative, administrative and organizational, technical-legal and personal. It concludes for the importance of the identification of this list of competencies to be required of this judge in his jurisdictional practice as parameters that can serve as references for the selection and training processes of the Brazilian judiciary.